Olivine ferric phosphate sodium composite material as well as preparation method and application thereof

By using nano-scale materials and organic sodium salts in olivine iron phosphate for ion permeation and sintering, combined with the use of coating agents, the problems of uneven sodium intercalation and poor electrochemical performance in chemical ion exchange methods are solved, and efficient sodium intercalation and material stability are achieved.

CN119905535AActive Publication Date: 2025-04-29四川易纳能新能源科技有限公司

Patent Information

Application Number
CN202311414759.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

In the prior art, the chemical ion exchange method has poor uniformity and low sodium penetration amount, resulting in poor electrochemical performance of the material and changes in the surface of the material affect the cycling stability of the battery.

Method used

Nano-scale olivine iron phosphate, organic sodium salt and reducing agent are used to perform ion permeation in the first solvent, and the solvent is removed and sintered to form a precursor of olivine sodium phosphate, and then coated with a coating agent to form a composite material of olivine sodium phosphate.

Benefits of technology

The embedding efficiency and embedding amount of sodium ions are improved, the conductivity and stability of the material are enhanced, the charge and discharge capacity and cycle stability are improved, and the positive electrode material performance of sodium ion batteries is better.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905535A_ABST
    Figure CN119905535A_ABST
Patent Text Reader

Abstract

The invention provides an olivine sodium ferric phosphate composite material as well as a preparation method and application thereof, and particularly relates to the technical field of sodium ion batteries. The preparation method comprises the following steps: A, adding nanoscale olivine iron phosphate, an organic sodium salt and a reducing agent into a first solvent, uniformly stirring, heating for ion permeation, removing the first solvent, and drying the product for the first time to obtain an olivine sodium iron phosphate precursor; b, sintering the olivine sodium ferric phosphate precursor in a protective atmosphere to obtain olivine sodium ferric phosphate; and C, dispersing the olivine sodium ferric phosphate in a second solvent to prepare a solution, dropwise adding a coating agent into the solution, sealing and coating, and then filtering, cleaning, secondarily drying, grinding and calcining to obtain the olivine sodium ferric phosphate composite material. According to the preparation method, the sodium embedding amount and the sodium embedding uniformity are improved, and the stability of the composite material is improved. The preparation method is simple to operate, continuous in process, high in process controllability and beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an olivine sodium iron phosphate composite material and a preparation method and application thereof. Background Art

[0002] Olivine-type NaFePO4 cathode materials have high theoretical specific capacity, good structural stability, thermal stability, and are also safe, non-toxic, and inexpensive, and are of great interest to researchers.

[0003] However, it was found during the preparation process that the olivine-structured NaFePO4 is thermodynamically extremely unstable and can be easily transformed into a stable but electrochemically inactive sodium iron phosphate-type NaFePO4 upon sintering. Therefore, it cannot be directly obtained by the traditional solid-phase sintering method. In addition, the electronic and ionic conductivity of the material is poor, which greatly limits the Na + of embedding and extraction.

[0004] At present, most of the research mainly prepares olivine sodium iron phosphate through electrochemical method, by charging lithium iron phosphate, releasing lithium ions, obtaining olivine iron phosphate, and then providing sodium ions through the negative electrode for discharge, so that the sodium ions are embedded in the iron phosphate, and finally obtaining olivine sodium iron phosphate. This method is difficult to operate, not conducive to industrial production, and has high cost. In view of this, many researchers have begun to try new ion exchange methods to obtain olivine sodium iron phosphate. The chemical ion exchange method is to use an oxidant to delithiate LiFePO4 to obtain olivine FePO4, and then introduce sodium salt for simple mixed sintering to embed sodium, but this sodium embedding method ignores the effectiveness of sodium embedding. Because the mixing method is rough, the uniformity of element distribution is reduced, the sodium embedding is uneven and the amount of sodium embedding is low, resulting in low charge and discharge capacity of the material after sintering; on the other hand, the chemical ion exchange method will cause changes in the activity of the material surface, especially after sodium embedding, the surface stability of the material becomes worse, and the embedded sodium ions will slowly migrate to the surface of the material, reacting with water and carbon dioxide in the air to form sodium hydroxide and sodium carbonate, thereby reducing the electrochemical capacity of the material; at the same time, the surface is highly alkaline and easily reacts with the electrolyte, resulting in continuous attenuation of the battery capacity and poor cycle stability.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing an olivine sodium iron phosphate composite material, aiming to solve the technical problems in the prior art that the chemical ion exchange method has poor uniformity and low sodium insertion amount, and the chemical ion exchange method causes changes in material activity and affects the electrochemical performance of the battery.

[0007] A second object of the present invention is to provide an olivine sodium iron phosphate composite material.

[0008] The third object of the present invention is to provide an application of an olivine sodium iron phosphate composite material in a positive electrode of a sodium ion battery.

[0009] In order to solve the above technical problems, the present invention particularly adopts the following technical solutions:

[0010] A first aspect of the present invention provides a method for preparing an olivine sodium iron phosphate composite material, comprising the following steps:

[0011] A. adding nano-sized olivine iron phosphate, an organic sodium salt and a reducing agent to a first solvent and stirring evenly, heating for ion penetration, removing the first solvent and drying the product for the first time to obtain an olivine sodium iron phosphate precursor;

[0012] B. sintering the olivine sodium iron phosphate precursor under a protective atmosphere to obtain olivine sodium iron phosphate;

[0013] C. dispersing the olivine sodium iron phosphate in a second solvent to prepare a solution, dripping a coating agent into the solution and sealing it for coating, filtering and washing, performing a second drying, grinding, and calcining to obtain the olivine sodium iron phosphate composite material.

[0014] Furthermore, the molar ratio of the olivine iron phosphate to the organic sodium salt is 1:0.5-1.2.

[0015] The amount of the reducing agent added is 5%-15% of the mass of the olivine iron phosphate.

[0016] The amount of the first solvent added is 1.5-6 times the mass of the olivine iron phosphate.

[0017] Furthermore, in step C, the amount of the coating agent added is 0.5%-5% of the mass of the olivine sodium iron phosphate.

[0018] The coating agent includes at least one of aluminum fluoride, sodium phosphate, sodium oxalate, sodium acetate, aluminum oxide, sodium polyacrylate, pentasodium diethylenetriamine penta (methylene phosphonate), sodium carboxymethyl cellulose, sodium fluoride, sodium aluminate, polyaniline, polypyrrole, polypyridine and polydopamine.

[0019] The second solvent includes at least one of acetone, ethanol, isopropanol and n-propanol.

[0020] Furthermore, the particle size of the nano-olivine iron phosphate is 50nm-300nm.

[0021] The organic sodium salt includes at least one of sodium acetate, sodium citrate, sodium oxalate, sodium formate, sodium gluconate, sodium malate, sodium benzoate, sodium p-hydroxybenzoate, sodium ethyl p-hydroxybenzoate, sodium ethylparaben, and sodium oleate.

[0022] The reducing agent includes at least one of PEG, acrylate, methylpentanol and fatty acid polyethylene glycol ester.

[0023] The first solvent includes water or a mixed solvent of water and ethanol.

[0024] Furthermore, step A also includes adding a dispersant to the first solvent.

[0025] The dispersant includes at least one of PVP, PVA, CTAB and guar gum.

[0026] Furthermore, in step A, the temperature of the ion penetration is 50°C-90°C.

[0027] The temperature of the first drying is 80° C.-120° C., and the time is 8 h-16 h.

[0028] The means of removing the first solvent includes evaporation.

[0029] Furthermore, in step B, the sintering temperature is 300° C.-450° C., and the sintering time is 8 h-24 h.

[0030] In step C, the coating time is 2h-8h.

[0031] The calcination temperature is 150° C.-370° C., and the calcination time is 1 h-5 h.

[0032] The second aspect of the present invention provides an olivine sodium iron phosphate composite material prepared by the preparation method.

[0033] Furthermore, it includes a core layer and a cladding layer.

[0034] The material of the core layer is olivine sodium iron phosphate.

[0035] The material of the coating layer includes at least one of aluminum fluoride, sodium phosphate, sodium oxalate, sodium acetate, aluminum oxide, sodium polyacrylate, pentasodium diethylenetriamine penta (methylene phosphonate), sodium carboxymethyl cellulose, sodium fluoride, sodium aluminate, polyaniline, polypyrrole, polypyridine and polydopamine.

[0036] The coating layer has a thickness of 1 nm to 20 nm.

[0037] The third aspect of the present invention provides the use of the olivine sodium iron phosphate composite material in the positive electrode of a sodium ion battery.

[0038] Compared with the prior art, the present invention has at least the following beneficial effects:

[0039] The preparation method of the olivine sodium iron phosphate composite material provided by the present invention, the reducing agent reduces the trivalent iron to divalent iron, and the missing lattice vacancies provide contact sites for sodium ions; the organic sodium salt is uniformly dispersed in the system of nano-scale olivine iron phosphate through ion penetration. Wherein the raw material adopts nano-scale iron phosphate, the smaller primary particle size can greatly shorten the path of sodium ion embedding, the larger specific surface area can increase the contact area and uniformity of iron phosphate and sodium salt, increase the ion embedding channel, thereby further improving the efficiency and amount of sodium embedding, and also reducing the difficulty of preparing the composite material in the later stage. After removing the first solvent, the organic sodium salt is covalently combined with the olivine ferrous phosphate to form an olivine sodium iron phosphate precursor. By sintering the olivine sodium iron phosphate precursor, anions and carbon are generated during the sintering process, and the carbon will reduce the unreduced trivalent iron to divalent iron, provide power for the embedding of sodium ions, and ensure the uniformity and embedding amount of sodium ions. The carbon and coating agent generated by sintering are coated on the surface of the material, further improving the conductivity and stability of the composite material, and improving the charge and discharge capacity and cycle stability of the composite material. The method is simple to operate, has a continuous process, has strong process controllability, and is conducive to industrial production.

[0040] The olivine sodium iron phosphate composite material provided by the present invention has a charge and discharge capacity of up to 141.59 mAh / g at 0.1C, a coulombic efficiency of up to 97.92%, a cycle retention rate of up to 98.38% after 200 cycles, and has good charge and discharge capacity and cycle stability.

[0041] The application provided by the present invention provides a positive electrode material with better performance for sodium ion batteries, promotes the development of sodium ion batteries towards high energy density and small volume, and expands the application scenarios of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 This is a SEM photo of the olivine iron phosphate used in the present invention;

[0044] Figure 2 This is a SEM photo of the composite material of olivine sodium iron phosphate obtained in Example 6;

[0045] Figure 3 The XRD pattern of olivine iron phosphate used in the present invention;

[0046] Figure 4XRD spectra of the olivine sodium iron phosphate composite material obtained in Examples 1 and 2 and the sodium iron phosphate composite material obtained in Example 11. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.

[0048] A first aspect of the present invention provides a method for preparing an olivine sodium iron phosphate composite material, comprising the following steps:

[0049] A. adding nano-sized olivine iron phosphate, an organic sodium salt and a reducing agent to a first solvent and stirring evenly, heating for ion penetration, removing the first solvent and drying the product for the first time to obtain an olivine sodium iron phosphate precursor;

[0050] B. sintering the olivine sodium iron phosphate precursor under a protective atmosphere to obtain olivine sodium iron phosphate;

[0051] C. Dispersing the olivine sodium iron phosphate in a second solvent to prepare a solution, dripping a coating agent into the solution to coat the olivine sodium iron phosphate, filtering and washing, second drying, grinding, and calcining to obtain the olivine sodium iron phosphate composite material.

[0052] The preparation method of the olivine sodium iron phosphate composite material provided by the present invention, the reducing agent reduces the trivalent iron to divalent iron, and the missing lattice vacancies provide contact sites for sodium ions; the organic sodium salt is uniformly dispersed in the olivine iron phosphate system through ion penetration. The raw material adopts nano-scale iron phosphate, which has a smaller primary particle size and a larger specific surface area, can greatly shorten the path of sodium ion embedding, increase the contact area and uniformity of iron phosphate and sodium salt, increase the ion embedding channel, thereby further improving the efficiency and amount of sodium embedding, and also reducing the difficulty of preparing the composite material in the later stage. After removing the first solvent, the organic sodium salt is covalently combined with the olivine ferrous phosphate to form an olivine sodium iron phosphate precursor. By sintering the olivine sodium iron phosphate precursor, anions and carbon are generated during the sintering process. The carbon will reduce the unreduced trivalent iron to divalent iron, provide power for the embedding of sodium ions, and ensure the uniformity and embedding amount of sodium ions. The carbon produced by sintering and the coating agent are coated on the surface of the material, further improving the conductivity and stability of the composite material, and improving the charge and discharge capacity and cycle stability of the composite material. The method is simple to operate, has a continuous process, has strong process controllability, and is conducive to industrial production.

[0053] In some embodiments of the present invention, a crushing process is further included after the first drying, the purpose of which is to improve the particle size of the olivine sodium iron phosphate composite material so that the prepared olivine sodium iron phosphate composite material continues to remain at the nanometer level.

[0054] In step C, the coating layer formed by the coating agent can not only prevent the precipitated sodium from reacting with water and carbon dioxide in the air to generate sodium hydroxide and sodium carbonate, thereby avoiding further reduction of active sodium and increasing the charging capacity of the material, but also the coating agent changes the surface environment and reduces the side reaction between the positive electrode material and the electrolyte, thereby improving the cycle performance.

[0055] Furthermore, the molar ratio of the olivine iron phosphate to the organic sodium salt is 1:0.5-1.2.

[0056] When the molar ratio of olivine iron phosphate to organic sodium salt is greater than 1:0.5, that is, when the amount of organic sodium salt is lower than the above ratio, the sodium ions are insufficient and the embedded amount is low, resulting in too low charge and discharge capacity of the material; when the molar ratio of olivine iron phosphate to organic sodium salt is less than 1:1.2, that is, when the amount of organic sodium salt is higher than the above ratio, the material will contain too many sodium ions, and the excess sodium ions will be enriched on the surface of the material, resulting in excessive residual alkali on the surface of the material, which is not conducive to battery cell processing and later electrochemical cycles.

[0057] Typically, but not limiting, the molar ratio of olivine iron phosphate to organic sodium salt may be, for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2.

[0058] The amount of the reducing agent added is 5%-15% of the mass of the olivine iron phosphate.

[0059] When the amount of reducing agent added is less than 5% of the mass of olivine iron phosphate, the reduction effect of trivalent iron in the iron phosphate is poor or cannot be completely reduced, resulting in insufficient kinetic energy for deep sodium embedding of sodium ions; when the amount of reducing agent added is higher than 15% of the mass of olivine iron phosphate, excess reducing agent will remain on the surface of the material in the form of impurities, causing the material's specific capacity to be low.

[0060] Typically, but not limiting, the reducing agent is added in an amount of 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14% or 15% by mass of the olivine iron phosphate.

[0061] The amount of the first solvent added is 1.5-6 times the mass of the olivine iron phosphate. The amount of the first solvent added is based on the solute not being precipitated, and a typical but non-limiting amount is 1.5 times, 2 times, 3 times, 4 times, 5 times or 6 times the mass of the olivine iron phosphate.

[0062] Furthermore, in step C, the amount of the coating agent added is 0.5%-5% of the mass of the olivine sodium iron phosphate.

[0063] When the amount of coating agent added is less than 0.5% of the mass of olivine sodium iron phosphate, the coating effect is poor and insufficient to isolate the erosion of the material surface by water and carbon dioxide in the air; when the amount of coating agent added is higher than 5% of the mass of olivine sodium iron phosphate, it will not only reduce the gram capacity of the material itself too much, but also cause excessive resistance to sodium ion migration during the charge and discharge cycle of the material, and ultimately cause excessive polarization of the material. Typically but not restrictive, the amount of coating agent added is 0.5%, 1%, 2%, 3%, 4% or 5% of the mass of olivine sodium iron phosphate.

[0064] The coating agent includes at least one of aluminum fluoride, sodium phosphate, sodium oxalate, sodium acetate, aluminum oxide, sodium polyacrylate, pentasodium diethylenetriamine penta (methylene phosphonate), sodium carboxymethyl cellulose, sodium fluoride, sodium aluminate, polyaniline, polypyrrole, polypyridine and polydopamine.

[0065] In some embodiments of the present invention, the coating agent can also be generated by reacting the first reagent and the second reagent, and the first reagent and the second reagent are each independently selected from phosphoric acid, oxalic acid, sodium formate, sodium acetate, hydrofluoric acid, acetic acid, aluminic acid, nano-alumina, polystyrene, diethylenetriamine penta (methylene phosphonic acid) or carboxymethyl cellulose, etc.

[0066] The second solvent includes at least one of acetone, ethanol, isopropanol and n-propanol.

[0067] Furthermore, the particle size of the nano-olivine iron phosphate is 50nm-300nm. Nano-scale iron phosphate has a smaller primary particle size, which can greatly shorten the path of sodium ion embedding. Its larger specific surface area can increase the contact area and uniformity between iron phosphate and sodium salt, increase the ion embedding channel, thereby further improving the sodium embedding efficiency and amount, and also reducing the difficulty of preparing the composite material in the later stage.

[0068] The organic sodium salt includes at least one of sodium acetate, sodium citrate, sodium oxalate, sodium formate, sodium gluconate, sodium malate, sodium benzoate, sodium p-hydroxybenzoate, sodium ethyl p-hydroxybenzoate, sodium ethylparaben, and sodium oleate.

[0069] Organic sodium salts are soluble in aqueous solution to a certain extent. Therefore, the olivine iron phosphate is mixed with the organic sodium salt and then added to a mixed solution of ethanol and water. The dissolved organic sodium salt can be evenly dispersed in the entire system, and then the solvent is evaporated to make the organic sodium salt evenly precipitate on the surface of the iron phosphate. After the solvent is evaporated, it is calcined at low temperature to carbonize and decompose the anions of the organic sodium salt without destroying the structure of the olivine iron phosphate, leaving the sodium ions to slowly embed into the lattice through thermal diffusion. Citric acid, acetic acid and oxalic acid have the characteristics of low decomposition temperature. They decompose H2O, CO2, CO, etc. at a temperature below 480°C, which can ensure that the olivine-type NaFePO4 will not be transformed into sodium ferrophosphate-type NaFePO4. At the same time, the excess C in the system can react with Fe in FePO4. 3+ Reduction and carbon coating are carried out to finally obtain an olivine-type NaFePO4 positive electrode material with a certain carbon coating.

[0070] The reducing agent includes at least one of PEG, acrylate, methylpentanol and fatty acid polyethylene glycol ester.

[0071] It should be noted that PEG refers to polyethylene glycol; PVP refers to polyvinyl pyrrolidone; PVA refers to polyvinyl alcohol; and CTAB refers to cetyltrimethylammonium bromide.

[0072] The first solvent includes water.

[0073] Furthermore, step A also includes adding a dispersant to the first solvent.

[0074] The dispersant includes at least one of PVP, PVA, CTAB and guar gum. The dispersant makes the olivine iron phosphate dispersed evenly in the system without agglomeration, so that the resistance and speed of ion penetration into the olivine iron phosphate are equivalent, so that sodium can fully penetrate into all olivine iron phosphate molecules in the system.

[0075] Furthermore, in step A, the temperature of the ion penetration is 50°C-90°C. When the temperature of the ion penetration is lower than 50°C, the solvent evaporates too slowly, affecting the efficiency of material preparation; when the temperature of the ion penetration is higher than 90°C, some dispersants and reducing agents may deteriorate or become ineffective. Typically but not restrictively, the temperature of the ion penetration may be, for example, 50°C, 60°C, 70°C, 80°C or 90°C. The time of ion penetration is not specifically limited in the present invention, and is based on the time of evaporating the solvent.

[0076] The temperature of the first drying is 80°C-120°C, and the time is 8h-16h. The purpose of the first drying is to dry the product.

[0077] The means of removing the first solvent includes evaporation.

[0078] Further, in step B, the sintering temperature is 300°C-450°C, and the time is 8h-24h. When the sintering temperature is lower than 300°C, the anions, reducing agents, and dispersants in the organic sodium salt cannot be effectively carbonized, which not only causes the impurity content of the material to be high, but also cannot effectively reduce trivalent iron, affecting the amount of sodium embedding; when the sintering temperature is higher than 450°C, the olivine iron phosphate structure is unstable, causing the structure to collapse and lose electrochemical activity. Typically but not restrictive, the sintering temperature can be, for example, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C or 450°C, and the time can be, for example, 8h, 9h, 10h, 11h, 12h or 24h.

[0079] In step C, the coating time is 2h-8h.

[0080] The calcination temperature is 150°C-370°C, and the time is 1h-5h. The purpose of calcination is to remove the residual organic solvent inside the material and the coating layer and the excess organic groups on the coating layer to obtain a dense and stable coating layer. Typically but not limiting, the calcination temperature can be, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 340°C, 350°C, 360°C and 370°C, and the time can be, for example, 1h, 2h, 3h, 4h or 5h.

[0081] The second aspect of the present invention provides an olivine sodium iron phosphate composite material prepared by the preparation method.

[0082] The olivine sodium iron phosphate composite material provided by the present invention has a charge and discharge capacity of up to 141.59 mAh / g at 0.1C, a coulombic efficiency of up to 97.92%, a cycle retention rate of up to 98.38% after 200 cycles, and has good charge and discharge capacity and cycle stability.

[0083] Furthermore, it includes a core layer and a cladding layer.

[0084] The material of the core layer is olivine sodium iron phosphate.

[0085] The material of the coating layer includes at least one of aluminum fluoride, sodium phosphate, sodium oxalate, sodium acetate, aluminum oxide, sodium polyacrylate, pentasodium diethylenetriamine penta (methylene phosphonate), sodium carboxymethyl cellulose, sodium fluoride, sodium aluminate, polyaniline, polypyrrole, polypyridine and polydopamine.

[0086] The coating layer has a thickness of 1nm-20nm. The thickness of the coating layer is related to the amount of coating agent added. When the coating layer is less than 1nm thick, the coating layer is too thin to alleviate the problem of sodium precipitation. When the coating layer is more than 20nm thick, the gram capacity of the material itself will be reduced too much, and the sodium ion migration resistance of the material will be too large during the charge and discharge cycle, which will eventually cause excessive polarization of the material.

[0087] Typically, but not limiting, the coating layer may have a thickness of, for example, 1 nm, 3 nm, 5 nm, 7 nm, 9 nm, 11 nm, 13 nm, 15 nm, 17 nm, 19 nm or 20 nm.

[0088] The third aspect of the present invention provides the use of the olivine sodium iron phosphate composite material in the positive electrode of a sodium ion battery.

[0089] The application provided by the present invention provides a positive electrode material with better performance for sodium ion batteries, promotes the development of sodium ion batteries towards high energy density and small volume, and expands the application scenarios of sodium ion batteries.

[0090] In the following, some embodiments of the present invention are described in detail in conjunction with the embodiments. In the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. The raw materials used in the present invention can be obtained by commercial purchase unless otherwise specified.

[0091] Example 1

[0092] This embodiment provides an olivine sodium iron phosphate composite material, and the preparation process is as follows:

[0093] 1. Add 20.9g of olivine FePO4, 12.6g of sodium acetate and 1.6g of polyethylene glycol to 40g of pure water and stir. Then place the mixed solution in a 70℃ water bath and heat and stir until the solvent is evaporated. After drying in a 90℃ vacuum drying oven for 12h, transfer to a ball mill and ball mill at 400rpm for 2h. Sinter the ground material in a N2 atmosphere at a sintering temperature of 350℃ for 10h. After calcination, naturally cool to room temperature to obtain olivine NaFePO4.

[0094] 2. Take 40g of NaFePO4, 1.34g of oxalic acid and 50g of ethanol and stir them in a beaker. At the same time, add 2.45g of sodium acetate into the beaker, seal and stir for 5 hours, filter, wash with ethanol and vacuum dry, transfer to a ball mill and ball mill at 400rpm for 2 hours, calcine the ground material at 300℃ for 2 hours and cool it naturally to room temperature to obtain a secondary sintered NaFePO4 with a dense coating layer, i.e., olivine sodium iron phosphate composite material.

[0095] Example 2

[0096] This embodiment provides an olivine sodium iron phosphate composite material, and the preparation process is as follows:

[0097] 1. Add 30g of olivine FePO4, 16.8g of sodium oxalate and 2.3g of polyethylene glycol into 132g of pure water and stir. Then place the mixed solution in a 70℃ water bath and heat and stir until the solvent is evaporated. After drying in a 90℃ vacuum drying oven for 12h, transfer it to a ball mill and mill it at 400rpm for 2h. Sinter the ground material in a N2 atmosphere at a sintering temperature of 350℃ for 10h. After calcination, naturally cool it to room temperature to obtain olivine NaFePO4.

[0098] 2. Same as the step in Example 1.

[0099] Example 3

[0100] This embodiment provides an olivine sodium iron phosphate composite material, and the preparation process is as follows:

[0101] 1. Add 20.9g of olivine FePO4, 12.6g of sodium acetate and 1.6g of polyethylene glycol to 40g of pure water and stir. Then place the mixed solution in a 70℃ water bath and heat and stir until the solvent is evaporated. After drying in a 90℃ vacuum drying oven for 12h, transfer to a ball mill and ball mill at 400rpm for 2h. Sinter the ground material in a N2 atmosphere at a sintering temperature of 450℃ for 10h. After calcination, naturally cool to room temperature to obtain olivine NaFePO4.

[0102] 2. Same as the step in Example 1.

[0103] Example 4

[0104] This embodiment provides an olivine sodium iron phosphate composite material. The difference from Example 1 is that the amount of sodium acetate used in step 1 is 6.3 g, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0105] Example 5

[0106] This embodiment provides an olivine sodium iron phosphate composite material. The difference from Example 1 is that the amount of sodium acetate used in step 1 is 13.6 g, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0107] Example 6

[0108] This embodiment provides an olivine sodium iron phosphate composite material. The difference from Embodiment 1 is that 0.2 g PVA is further added to the pure water in Step 1. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described in detail here.

[0109] Example 7

[0110] This embodiment provides an olivine sodium iron phosphate composite material. The difference from Example 1 is that the amount of polyethylene glycol used in step 1 is 0.8 g, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0111] Example 8

[0112] This embodiment provides an olivine sodium iron phosphate composite material. The difference from Example 1 is that the amount of polyethylene glycol used in step 1 is 2.4 g, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0113] Example 9

[0114] This embodiment provides an olivine sodium iron phosphate composite material, and the preparation process is as follows:

[0115] 1. Same as the step in Example 1.

[0116] 2. The obtained NaFePO4 is 40g, 0.4g of nano-alumina and 50g of ethanol are stirred in a beaker, sealed and stirred for 5 hours, then filtered, washed with ethanol and vacuum dried, transferred to a ball mill and ball milled at 400rpm for 2 hours, and the ground material is calcined at 300°C for 2 hours and then naturally cooled to room temperature to obtain a secondary sintered NaFePO4 with a dense coating layer, i.e., an olivine sodium iron phosphate composite material.

[0117] Example 10

[0118] This embodiment provides an olivine sodium iron phosphate composite material, and the preparation process is as follows:

[0119] 1. Same as the step in Example 1.

[0120] 2. The obtained NaFePO4 is 40g, 2g of nano-alumina and 50g of ethanol are stirred in a beaker, sealed and stirred for 5 hours, then filtered, washed with ethanol and vacuum dried, transferred to a ball mill and ball milled at 400rpm for 2 hours, and the ground material is calcined at 300°C for 2 hours and then naturally cooled to room temperature to obtain a secondary sintered NaFePO4 with a dense coating layer, i.e., an olivine sodium iron phosphate composite material.

[0121] Embodiment 11

[0122] This embodiment provides a sodium iron phosphate composite material. The difference from Embodiment 1 is that the sintering temperature in step 1 is 600° C. and the holding time is 10 h. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described in detail here.

[0123] Comparative Example 1

[0124] This comparative example provides an olivine sodium iron phosphate, which is different from Example 1 in that there is no coating process in step 2, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0125] Comparative Example 2

[0126] This comparative example provides an olivine sodium iron phosphate composite material. The difference from Example 1 is that the reducing agent polyethylene glycol is not added in step 1, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.

[0127] Comparative Example 3

[0128] This comparative example provides a sodium iron phosphate, and the preparation process is as follows: 30g of olivine FePO4 and 16.8g of sodium oxalate are weighed, mixed and transferred to a ball mill for ball milling at 400rpm for 4h, and then the mixed material is sintered in a N2 atmosphere at a sintering temperature of 350°C and a holding time of 10h. After the calcination is completed, it is naturally cooled to room temperature to obtain NaFePO4.

[0129] Test Example 1

[0130] The olivine iron phosphate used in the examples and comparative examples was imaged by scanning electron microscopy (FESEM, JSM-6700F). Figure 1 As shown. Figure 1 As shown, the olivine iron phosphate is obtained after the lithium iron phosphate of olivine is delithiated. The iron phosphate after delithiation still maintains certain regular rod-like morphology agglomeration, indicating that the delithiation process does not affect the morphology of the material, and it can be observed from the scanning image that the size of the primary particles of the iron phosphate is uniformly between 50-300nm.

[0131] The olivine sodium iron phosphate composite material obtained in Example 6 was subjected to scanning electron microscopy (FESEM, JSM-6700F), and the obtained image is as follows: Figure 2 As shown. Figure 2 As shown, it can be seen that the primary particles after sodium insertion still retain the morphological characteristics before sodium insertion, and it can be clearly seen that the surface of the primary particles is covered with a dense coating layer.

[0132] Test Example 2

[0133] The olivine iron phosphate used in the examples and comparative examples was subjected to X-ray diffraction (SHIMADZU XRD-7000) test. The experimental conditions were as follows: copper target (λ = 0.1518 nm), 2θ angle range of 5° to 70°. The XRD spectrum is shown in Figure 3 shown.

[0134] from Figure 3It can be seen from the XRD spectrum in that the olivine iron phosphate used in the embodiment and the comparative example has characteristic peaks unique to olivine iron phosphate, which corresponds one-to-one with the standard card (PDF standard card number: PDF#97-009-2199), and belongs to the Pnma space point group. This result shows that the olivine iron phosphate used in the embodiment and the comparative example of the present invention has the same structure as the standard olivine iron phosphate.

[0135] X-ray diffraction (SHIMADZU XRD-7000) was performed on the olivine sodium iron phosphate composite material obtained in Examples 1 and 2 and the sodium iron phosphate composite material obtained in Example 11. The experimental conditions are as follows: copper target (λ = 0.1518 nm), 2θ angle range of 5° to 70°. The XRD spectrum is as follows Figure 4 shown.

[0136] from Figure 4 It can be seen from the XRD spectrum in that the olivine sodium iron phosphate composite material obtained in Examples 1 and 2 has characteristic peaks unique to olivine sodium iron phosphate, and no other impurity peaks, indicating that the structure of the material has not been changed after coating, and the characteristic peaks correspond to the standard card one by one (PDF standard card number: PDF#97-016-9188). The result shows that the olivine sodium iron phosphate composite material obtained in Examples 1 and 2 of the present invention is consistent with the structure of the standard olivine-type NFP. The sodium iron phosphate composite material obtained in Example 11 has characteristic peaks of the phosphotyrite structure, belongs to the Pmnb space point group, and corresponds to the characteristic peaks of the phosphotyrite sodium iron phosphate standard card one by one (PDF standard card number: PDF#29-1216). It shows that the sodium iron phosphate obtained in Example 11 is a phosphotyrite type.

[0137] Test Example 1

[0138] Take 0.4g of the materials provided in Examples 1-11 and Comparative Examples 1-3, 0.05g of a conductive agent (acetylene black), and 0.05g of a binder polyvinylidene fluoride (PVDF), and mix them in 0.5g of N-methylpyrrolidone (NMP) to obtain the desired positive electrode slurry. Subsequently, the slurry was coated on the treated aluminum foil and dried in a vacuum drying oven at 90°C for 10h to obtain a positive electrode sheet. The above-mentioned electrode sheet and sodium sheet were assembled into a button battery in a glove box. The electrolyte was 1mol·L -1 The sodium salt of NaPF6 is dissolved in a solution of ethylene carbonate (EC) and ethylene methyl carbonate (EMC) in a volume ratio of 1:1, and an additional 5% fluoroethylene carbonate (FEC) additive is added to the electrolyte. Subsequent electrochemical performance tests will focus on button cells.

[0139] The button cell was subjected to charge and discharge tests. The current was 13.0 mA / g at 0.1C, and the charge and discharge temperature was room temperature. The charge and discharge specific capacity and first cycle coulomb efficiency of the button cell were measured, and the results are shown in Table 1.

[0140] Table 1

[0141]

[0142]

[0143] As can be seen from Table 1, the amount of sodium salt added has a significant effect on the performance of the material. In Example 4, less sodium salt is used, the sodium ions in the system are insufficient, and the embedding amount is low, resulting in a low charge and discharge capacity of the material. During discharge, the sodium in the sodium sheet will be embedded in the positive electrode material, thereby causing a large discharge capacity, and the first efficiency exceeds 100%; when the sodium salt is excessive in Example 5, there are too many sodium ions in the system, and the excess sodium ions will be enriched on the surface of the material, resulting in excessive residual alkali on the surface of the material, which is not conducive to subsequent battery processing and electrochemical cycling. At the same time, it can be seen that the calcination temperature has a great influence on sodium iron phosphate. When the temperature is higher than 450°C, olivine-type sodium iron phosphate is very easy to be transformed into sodium iron phosphate of pyrite type and lose its electrochemical activity, and the charge and discharge capacity is extremely low. When sodium acetate is used to embed sodium, adding a certain amount of dispersant in the system of Example 6 will have a positive effect on the performance of the material. At the same time, the amount of reducing agent added will affect the embedding depth of sodium ions. When the amount of reducing agent added in Example 7 is small, the reduction effect of trivalent iron in iron phosphate is poor or cannot be completely reduced. When the reducing agent in Example 8 is added in excess, the excess reducing agent will remain on the surface of the material in the form of impurities, causing the material to have a low capacity. At the same time, by comparing Example 2 and Comparative Example 3, it can be seen that the sodium iron phosphate prepared by only a simple ball milling mixed sintering method has poor performance of the final material because the ions fail to penetrate into the iron phosphate and the ions are unevenly distributed.

[0144] In Comparative Examples 1-3, the first efficiency of the materials is higher than 100%. This is because there is no dense coating layer on the surface of the material that has not been coated and sintered. The embedded sodium ions will slowly migrate to the surface of the material, making the sodium ion content inside the material insufficient. During the withholding test, the sodium in the sodium sheet of the negative electrode will be excessively embedded in the material during the discharge process, making the first charging capacity greater than the first discharge capacity, resulting in a first efficiency higher than 100%.

[0145] Test Example 2

[0146] The button cell obtained in Experimental Example 1 was subjected to a cycle performance test. The current 1C was 130 mA / g, and the charge and discharge temperature was room temperature. Before the 1C formal cycle, it was activated with a small current of 0.1C for 3 cycles. The discharge specific capacity of the button cell was measured, and the discharge specific capacity was continued to be measured after 200 cycles. The capacity retention rate was calculated, and the results are shown in Table 2.

[0147] Table 2

[0148]

[0149]

[0150] It can be seen from Table 2 that when the amount of sodium salt added in Example 4 is insufficient, the sodium in the sodium sheet will be embedded in the material during discharge, and the charge and discharge efficiency is less than 100% from the second cycle of charging. However, due to the insufficient amount of organic sodium salt added, the amount of coated carbon is reduced, which has a negative impact on the cycle performance to a certain extent. It can be seen from Comparative Example 1 and Example 1 that the cycle performance of the material after secondary coating and sintering is better than that of the uncoated material. This is because the surface of the uncoated material in Comparative Example 1 has high alkalinity and is easy to react with the electrolyte, resulting in continuous attenuation of the battery capacity and poor cycle stability.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an olivine sodium iron phosphate composite material, characterized in that: The following steps are involved: A. adding nano-sized olivine iron phosphate, an organic sodium salt and a reducing agent to a first solvent and stirring evenly, heating for ion penetration, removing the first solvent and drying the product for the first time to obtain an olivine sodium iron phosphate precursor; B. sintering the olivine sodium iron phosphate precursor under a protective atmosphere to obtain olivine sodium iron phosphate; C. Dispersing the olivine sodium iron phosphate in a second solvent to prepare a solution, dripping a coating agent into the solution to coat the olivine sodium iron phosphate, filtering and washing, second drying, grinding, and calcining to obtain the olivine sodium iron phosphate composite material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the olivine iron phosphate to the organic sodium salt is 1:0.5-1.2; The amount of the reducing agent added is 5%-15% of the mass of the olivine iron phosphate; The amount of the first solvent added is 1.5-6 times the mass of the olivine iron phosphate.

3. The preparation method according to claim 1, characterized in that: In step C, the amount of the coating agent added is 0.5%-5% of the mass of the olivine sodium iron phosphate; The coating agent comprises at least one of aluminum fluoride, sodium phosphate, sodium oxalate, sodium acetate, aluminum oxide, sodium polyacrylate, pentasodium diethylenetriamine penta (methylene phosphonate), sodium carboxymethyl cellulose, sodium fluoride, sodium aluminate, polyaniline, polypyrrole, polypyridine and polydopamine; The second solvent includes at least one of acetone, ethanol, isopropanol and n-propanol.

4. The preparation method according to claim 1, characterized in that: The particle size of the nano-olivine iron phosphate is 50nm-300nm; The organic sodium salt comprises at least one of sodium acetate, sodium citrate, sodium oxalate, sodium formate, sodium gluconate, sodium malate, sodium benzoate, sodium p-hydroxybenzoate, sodium ethyl p-hydroxybenzoate, sodium ethyl hydroxybenzoate, and sodium oleate; The reducing agent comprises at least one of PEG, acrylate, methylpentanol and fatty acid polyethylene glycol ester; The first solvent includes water or a mixed solution of water and ethanol.

5. The preparation method according to claim 1, characterized in that: In step A, a dispersant is added to the first solvent; The dispersant includes at least one of PVP, PVA, CTAB and guar gum.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step A, the ion penetration temperature is 50°C-90°C; The first drying temperature is 80°C-120°C and the time is 8h-16h; The means of removing the first solvent includes evaporation.

7. The preparation method according to any one of claims 1 to 5, characterized in that: In step B, the sintering temperature is 300°C-450°C and the sintering time is 8h-24h; In step C, the coating time is 2h-8h; The calcination temperature is 150° C.-370° C., and the calcination time is 1 h-5 h.

8. An olivine sodium iron phosphate composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The olivine sodium iron phosphate composite material according to claim 8, characterized in that: including a core layer and a cladding layer; The material of the core layer is olivine sodium iron phosphate; The material of the coating layer includes at least one of aluminum fluoride, sodium phosphate, sodium oxalate, sodium acetate, aluminum oxide, sodium polyacrylate, pentasodium diethylenetriamine penta (methylene phosphonate), sodium carboxymethyl cellulose, sodium fluoride, sodium aluminate, polyaniline, polypyrrole, polypyridine and polydopamine; The coating layer has a thickness of 1 nm to 20 nm.

10. Use of the olivine sodium iron phosphate composite material prepared by the preparation method according to any one of claims 1 to 7, or the olivine sodium iron phosphate composite material according to claim 8 or 9 in a positive electrode of a sodium ion battery.

Citation Information

Patent Citations

  • Carbon-coated sodium ferrous fluorophosphate positive electrode active material, preparation thereof and application of carbon-coated sodium ferrous fluorophosphate positive electrode active material in sodium ion battery

    CN114122311A

  • Nanoscale olivine-type sodium ferric phosphate as well as preparation method and application thereof

    CN114572956A

  • Synthesis method of positive electrode material sodium ferric phosphate for sodium ion battery

    CN114759179A

  • Preparation process of high-stability sodium ion battery positive electrode material and sodium ion battery

    CN115472825A

  • Olivine sodium iron phosphate with polymer coating, sodium iron battery comprising the same as cathode material, and process thereof

    KR1020160136809A

Cited By

  • Preparation method of olivine-type sodium ferric phosphate, olivine-type sodium ferric phosphate and sodium ion battery

    CN121376945A